2020
DOI: 10.3174/ajnr.a6651
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Neurologic Complication with CNS Vasculitis-Like Pattern

Abstract: Coronavirus disease 2019 (COVID-19) is a viral infection caused by the Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2), which spreads rapidly from person to person and manifests in most symptomatic patients as a respiratory illness, similar to prior SARS viruses. Neurologic manifestations of COVID-19 are uncommon; those so far reported include encephalopathy, stroke from large-vessel occlusion, and polyneuropathy. We report a unique neurologic complication of COVID-19 in a patient who had extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 19 publications
5
142
1
4
Order By: Relevance
“…ACE2 receptor has higher expression in neurons and cerebral vessel endothelial cells which can cause high level of CNS invasion. [185,186] Histologic evidence of COVID-19-induced vasculitis has been reported in several other organs including lung, kidney, liver and skin. [186] Similarly, virus-related endothelial injury and endotheliitis might cause CNS vasculitis.…”
Section: Cns Vasculitismentioning
confidence: 99%
See 1 more Smart Citation
“…ACE2 receptor has higher expression in neurons and cerebral vessel endothelial cells which can cause high level of CNS invasion. [185,186] Histologic evidence of COVID-19-induced vasculitis has been reported in several other organs including lung, kidney, liver and skin. [186] Similarly, virus-related endothelial injury and endotheliitis might cause CNS vasculitis.…”
Section: Cns Vasculitismentioning
confidence: 99%
“…Hanafi R, et al [185] reported a 65-year-old man with COVID-19 who had extensive diffuse subcortical ischemic lesions in the brain resembling cerebral vasculitis. (Figure 8) He also developed a characteristic lower extremity skin rash.…”
Section: Cns Vasculitismentioning
confidence: 99%
“…However, the 18-year-old boy died at home, 11 days after discharge. Autopsy of the brain showed cerebral vasculitis probably associated with COVID-19 [24,25].…”
Section: Characteristics Of Patients Admitted With Covid-19mentioning
confidence: 99%
“…The pathophysiology is not yet fully understood and may be multifactorial including microthrombosis with secondary haemorrhage, dysregulated coagulation, e.g. disseminated intravascular coagulation and immune thrombocytopenic purpura [5], and vascular hyperpermeability in the context of COVID-19 cytokine storm [1], endotheliitis [6] and vasculitis [7].…”
Section: Introductionmentioning
confidence: 99%